Effectiveness of a training program for community-based resource workers on cleft lip and palate and cleft speech - Subha Shunmugam; B Subramaniyan; Roopa Nagarajan; Savitha Vadakkanthara Hariharan (Wolters Kluwer Medknow Publications, 2017)
Objective: This study evaluated the training module which was developed for resource workers in the community, to impart knowledge about cleft lip and/or palate (CLP) and skill to identify error patterns in speech of individuals with CLP. Design: This was a cross-sectional study. Method: This study is a part of an ongoing community based rehabilitation project conducted in a rural district of South India. A total of 47 resource workers belonging to a rural district served as participants of this study. Pre and post training measures were compared to examine the effectiveness of the training program. Knowledge about CLP and ability to identify error patterns in speech of individuals with CLP by the resource workers were measured pre and post training to examine the effectiveness of the training program. Results: There was a statistically significant improvement in the resource workers' knowledge about CLP. Resource workers were able to identify the abnormal productions but were inconsistent in categorizing the specific error patterns. Conclusions: The post training results revealed improvement in the resource worker's understanding of CLP and ability to identify speech patterns in individuals with CLP. It can be inferred that with periodic retraining, resource workers can be trained to identify speech error patterns in individuals with CLP. Trained resource workers could probably be used to provide speech services under the supervision of speech-language pathologist (SLP) in places where SLPs are not available locally to provide direct therapy.